Wave impact on a vertical baffle - Nor Aida Zuraimi, Md Noar; Greenhow, Martin (Asian Research Publishing Network, 2016)
We consider the wave impact against a vertical baffle or a vertical wall in close proximity to the baffle for four cases: (i) a vertical baffle at free surface; (ii) a vertical baffle in front of a wall; (iii) a vertical baffle on a deck in front of a wall; (iv) a vertical baffle on the tank bottom in front of a wall. The mathematical formulation and the boundary conditions for four cases are presented for the pressure impulse. We used a basis function solution method for the pressure impulse which can then be integrated analytically to give the total impulse for each problem. These basis functions satisfy the boundary conditions except on the baffle and a matching line, where appropriate conditions give a matrix system for the unknown coefficients. The influence of the depth of baffle penetration and the size of the impact region is also studied. We find that pressure impulse with the same size of impact region on baffles of the same length are almost same for cases (i), (ii) and (iii). However the pressure impulse behind the baffles decreases when the length of the baffle increases for cases (ii) and (iii). For case (iv), the pressure impulse on the wall and behind the baffles increases when the length of the bottommounted baffle increases